Manajemen Diri Guru Penggerak Dalam Peningkatan Motivasi Belajar Peserta Didik di SMA Negeri 1 Tunjungan - Diannita, Artika (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2023)
This study aims to describe the self-management of driving teachers in increasing students' learning motivation at SMAN 1 Tunjungan Blora. This study uses a qualitative descriptive research method to determine the phenomena in the field related to the self-management of driving teachers so that the information obtained is factual and accurate. The population of this study was the driving forceteachers at SMAN 1 Tunjungan Blora, the sample used in this study was purposive sampling. Methods of data collection using observation, interviews, and primary and secondary data documentation. Data analysis techniques were carried out until the data was saturated, that is, if there was no other information or it was the same, both the data from the same informant and different informants. The research results show that; 1) Motivator teacher self-management increases student learning motivationby knowing the purpose of work as an educator, namely not only by educating but also building character, guiding students' nature, interests, and talents, 2) Motivating teacher self-management increases student learning motivation students by carrying out self-development through education and training (training), reading books and journals literacy, and increasing competence in the field of technology, 3) Self-management of driving teachers increases student learning motivation by cultivatingemotional intelligence through selfsoothing activities before starting learning in class and also take a personal approach for students who have problems in learning, 4) Self-management of the driving teacher increases student learning motivation by managing time through making time lists and using group methods in the defense process horse